2021
DOI: 10.3390/genes12111792
|View full text |Cite
|
Sign up to set email alerts
|

KCNG1-Related Syndromic Form of Congenital Neuromuscular Channelopathy in a Crossbred Calf

Abstract: Inherited channelopathies are a clinically and heritably heterogeneous group of disorders that result from ion channel dysfunction. The aim of this study was to characterize the clinicopathologic features of a Belgian Blue x Holstein crossbred calf with paradoxical myotonia congenita, craniofacial dysmorphism, and myelodysplasia, and to identify the most likely genetic etiology. The calf displayed episodes of exercise-induced generalized myotonic muscle stiffness accompanied by increase in serum potassium. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Whole-genome sequencing was performed as previously described (Jacinto et al, 2022). Reads were mapped to the ARS-UCD1.2 assembly (Rosen et al, 2020), resulting in an average read depth of 13×, and then processed as previously reported (Jacinto et al, 2021). This identified 30 homozygous private protein-changing variants that were present exclusively in the genome of the affected calf and absent in 942 controls from the ongoing Swiss Comparative Bovine Resequencing Project, including 28 genomes from purebred Limousine cattle (Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole-genome sequencing was performed as previously described (Jacinto et al, 2022). Reads were mapped to the ARS-UCD1.2 assembly (Rosen et al, 2020), resulting in an average read depth of 13×, and then processed as previously reported (Jacinto et al, 2021). This identified 30 homozygous private protein-changing variants that were present exclusively in the genome of the affected calf and absent in 942 controls from the ongoing Swiss Comparative Bovine Resequencing Project, including 28 genomes from purebred Limousine cattle (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…
MYH3-associated non-syndromic palatoschisis (cleft palate, CP) in Limousine cattle
BACKGROUNDPalatoschisis (also called cleft palate) is an opening or cleft in the upper lip, the roof of the palate, or both, and is a common defect in both humans and domestic animals (Mossey & Modell, 2012;Mulvihill et al, 1980). It can also occur in cattle as an isolated (non-syndromic) birth defect (OMIA 000197-9913), or it is associated with familial or sporadic genetic syndromes, such as the recessively inherited CHRNB1-related arthrogryposis multiplex congenita in Red dairy cattle (Agerholm et al, 2016; OMIA 000070-9913), or the reported isolated case of KCNG1-related neuromuscular channelopathy (Jacinto et al, 2021; OMIA 002483-9913).
…”
mentioning
confidence: 99%
“…A whole‐genome sequencing (WGS) approach was performed as described before (Jacinto et al, 2022 ) using genomic DNA extracted from blood of the affected calf, her dam, and from semen of her sire. Reads were mapped to the ARS‐UCD1.2 assembly (Rosen et al, 2020 ) resulting in an average read depth of 20.7× in the calf, 21.8× in the dam, and 22.1× in the sire, and then processed as reported earlier (Jacinto et al, 2021 ). We hypothesized that the affected calf had a novel form of dwarfism and investigated the genetic origin.…”
Section: Discussionmentioning
confidence: 99%
“…Reads were mapped to the ARS‐UCD1.2 assembly (Rosen et al, 2020), resulting in an average read depth of 14.7×. The WGS data were evaluated as previously described (Jacinto et al, 2021). Variant filtering did not reveal any private homozygous protein‐changing variants present in the genome of the affected calf, making a possible recessive inheritance unlikely.…”
Section: Discussionmentioning
confidence: 99%